New faunistic records of Curculionoidea (Coleoptera: Cucujiformia) from Oman - Ali Al-Jahdhami (Sociedade Entomológica do Brasil, 2021)
This communication reports on records of fourteen species and three morphospecies from Oman. Squamapion sp., Nanophyes sp., Schoenherr, 1838, Hoplopodapion tibesticola (Alonso-Zarazaga, 1983), Aegyptobaris arctithorax (Pic, 1899), Eumycterus albosquamulatus Boheman, 1838, Proeces filum (Marshall, 1933), Rhamphus micros Colonnelli, 2009, Sharpia sabulicola Colonnelli, 2009, Smicronyx (Smicronyx) rufipennis Tournier, 1874, Amblyrhinus cylindricollis Magnano, 2009, Myllocerus undecimpustulatus Faust, 1891, Cosmogaster cordofanus (Fåhraeus, 1842), Hypolixus nubilosus (Boheman, 1836), Microlarinus irregularis Colonnelli, 2009 are from northen Oman and Araecerus sp., Cylindroides bifasciatus (Quedenfeldt, 1887), Orfilaia arabica (Muizon, 1954) from Dhofar in southern Oman.